"HYGIENIC ASSESSMENT OF BACTERIOLOGICAL INDICATORS OF DRINKING WATER IN CHEMICAL, ORGANOLEPTIC BATHS" (ON THE EXAMPLE OF THE CITY OF TASHKENT) (World Bulletin of Public Health, 2024)
Water is important in human life.Its importance is very important not only to the life of Man and heaven, but also to the plant world. The issues of providing the population with quality drinking water and the health indicators of the population here, the elimination of many epidemic diseases, the improvement of residential areas and the provision of sanitary camphor of residential buildings are closely related
Keywords: buildings; sanitary; rinking water; health